2008
DOI: 10.1111/j.1365-2265.2008.03238.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous ethanol injection therapy: a surgery‐sparing treatment for primary hyperparathyroidism

Abstract: PEIT is a safe and effective nonsurgical treatment for patients with p-HPT, who are unsuitable for surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…A Currently, there is considerable interest in identifying therapeutic alternatives to surgery. There have been several reports on minimally invasive treatments of PHPT, such as ethanol ablation (12), laser ablation (13), radiofrequency ablation (RFA) (14), and high-intensity focused ultrasound (US) (15,16). As another minimally invasive treatment, microwave ablation (MWA) has also been used successfully in recent years (17)(18)(19).…”
Section: Mwa Proceduresmentioning
confidence: 99%
“…A Currently, there is considerable interest in identifying therapeutic alternatives to surgery. There have been several reports on minimally invasive treatments of PHPT, such as ethanol ablation (12), laser ablation (13), radiofrequency ablation (RFA) (14), and high-intensity focused ultrasound (US) (15,16). As another minimally invasive treatment, microwave ablation (MWA) has also been used successfully in recent years (17)(18)(19).…”
Section: Mwa Proceduresmentioning
confidence: 99%
“…However, chemical ablation (injection of ethanol, acetic acid or calcitriol) has the risk of solute leakage into the surrounding tissue, which could be harmful [32]. The incidence of injection-related complications with chemical ablation, such as hemorrhage, recurrent laryngeal nerve palsy caused by ethanol leakage, and adhesions to surrounding tissue, increases with the number of injections [32,33]. Our previous and other researcher's studies [16,34,35] also mentioned that MWA devices could create a uniform electromagnetic field surrounding the antenna.…”
Section: Discussionmentioning
confidence: 99%
“…In examining the indications for this procedure in patients with PHPT, Herman et al [6] had highlighted 4 indications: (1) medical comorbidities, (2) patient choice, (3) technically difficult surgery, and (4) partial ablation of the only remaining gland after previous subtotal parathyroidectomy for multiple gland disease [6]. PAA is less expensive, less invasive, requires less extensive preparation, and avoids the usual risks of surgery [7]. Furthermore, it was found that PAA increases neither the risk nor the difficulty of subsequent parathyroidectomy in cases in which the procedure fails to achieve normocalcemia and surgical intervention becomes possible [8].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was found that PAA increases neither the risk nor the difficulty of subsequent parathyroidectomy in cases in which the procedure fails to achieve normocalcemia and surgical intervention becomes possible [8]. Few complications have been reported with the procedure, including incomplete necrosis of the adenoma, temporary or rarely permanent recurrent laryngeal nerve injury [6], temporary hypocalcemia, and periglandular fibrosis [7][8][9]. Recurrence of hypercalcemia is common several months to years after ablation with alcohol, which is an indication for regular monitoring of serum calcium levels after the procedure.…”
Section: Discussionmentioning
confidence: 99%